Роль викладача в розвитку критичного мислення студентів на основі знань та взаєморозуміння - Михайленко, Олена Юріївна; Mykhailenko, Olena (Київ: Навчально науковий інститут публічного управління та державної служби Київського національного університету імені Тараса Шевченка, 2025)
UA: У 21 столітті перед людиною постали нові виклики, при чому не залежно від віку та професії – потреба розвивати критичне мислення. Навіщо? По-перше, тому що це розвиває м’язи мозку, запобігає таким хворобам як Альцгеймер, деменція, хвороба Паркінсона. По-друге, допомагає ефективніше мислити та швидше аналізувати інформацію. /// EN: In the 21st century, the development of critical thinking has become a necessity for everyone. It helps prevent brain diseases, develop independence, the ability to analyze information and resist manipulation. In the educational environment, the technology of critical thinking is important, based on three stages: challenge, comprehension, reflection. The teacher should create a safe atmosphere, encourage activity, stimulate reflection and dialogue, provide conditions for deep understanding and self-analysis.
The role of a vikladach for the development of students’ critical thinking based on knowledge and mutual interpretation
Keywords: інноваційні методи навчання; критичне мислення; вища освіта; освітні технології; innovative teaching methods; critical thinking; higher education; educational technologies